On Frame’s inequalities - Ling Zhu (Journal of Inequalities and Applications, 2018)
Abstract In this paper, the errors of the two inequalities in Theorem 3.4.20 in the classic “Analytic Inequalities” by Mitrinovic are corrected, and the corresponding inequalities for circular functions and hyperbolic functions are rebuilt.